AM HERCULIS IN 1989-93: VARIOUS TYPES OF PHOTOMETRIC AND POLARIMETRIC BEHAVIOUR - Shakhovskoy, N. M.; Andronov, I. L.; Kolesnikov, S. V. (Одеські астрономічні публікації, 2017)
The types of variability of AM Her are discussed on the base of monitoring carried out at the 2.6m Shajn and 1.25cm AZT-11 telescopes of the Crimean Astrophysical observatory. The main types are the following: a) the wavelength-dependent regular variations with the orbital phase more pronounced in RI bands and observed at high and intermediate luminosity states; b) at the low and intermediate states the variations in UB which are usually in antiphase with RI; c) flares caused by the accretion events with colors close to that of the system; d) flares of the secondary of the UV Cet-type.